KEPEMIMPINAN KOLABORATIF UNTUK MENGELOLA GENERASI Z DI TEMPAT KERJA: TANTANGAN DAN PELUANG TERKINI - Agung Prasetya; Mahdum Mahdum; Fadly Azhar; Dahnilsyah Dahnilsyah (STKIP Pesisir Selatan, 2025)
Generation Z is beginning to dominate the workforce and brings unique characteristics such as high digital literacy, a focus on flexibility, a need for meaningful work, and a preference for open and participatory communication. This situation requires organizations to adapt their leadership styles to optimally manage their potential. This study aims to analyze the application of collaborative leadership in managing the Generation Z workforce and identify emerging challenges and opportunities in efforts to improve motivation, productivity, and work engagement. This study used a literature review method by examining scientific articles, global employment survey reports, and academic studies related to leadership and workforce generations. The results show that collaborative leadership is effective in building an inclusive work culture, encouraging active participation, and increasing innovation through trust-based relationships and two-way communication. However, its implementation still faces challenges such as value gaps between generations, demands for rapid feedback, and structural adaptations in organizations that are still hierarchical. On the other hand, these challenges can be strategic opportunities through the use of collaborative technology, adaptive leadership training, and designing flexible work systems that suit the needs of the younger generation.